Chemical and biological study of aplysiatoxin derivatives showing inhibition of potassium channel Kv1.5. Issue 14 (6th March 2019) - Tang, Yang-Hua; Wu, Jing; Fan, Ting-Ting; Zhang, Hui-Hui; Gong, Xiao-Xia; Cao, Zheng-Yu; Zhang, Jian; Lin, Hou-Wen; Han, Bing-Nan
Abstract : New aplysiatoxin derivative (oscillatoxin E) exhibiting potent blocking activity against potassium channel Kv1.5 is consistent with molecular docking analysis. Abstract : Three new aplysiatoxins, neo-debromoaplysiatoxin D (1 ), oscillatoxin E (2 ) and oscillatoxin F (3 ), accompanied by four known analogues (4–7 ), were identified from the marine cyanobacterium Lyngbya sp. Structural frames differ amongst these metabolites, and therefore we classified compounds1 and4–6 as aplysiatoxins as they possess 6/12/6 and 6/10/6 tricyclic ring systems featuring a macrolactone ring, and compounds2, 3 and7 as oscillatoxins that feature a hexane-tetrahydropyran in a spirobicyclic system. Bioactivity experiments showed that compounds1 and4–6 presented significant expression of phosphor-PKCδ whereas compounds2, 5 and7 showed the most potent blocking activity against potassium channel Kv1.5 with IC50 values of 0.79 ± 0.032 μM, 1.28 ± 0.080 μM and 1.47 ± 0.138 μM, respectively. Molecular docking analysis supplementing the binding interaction of oscillatoxin E (2 ) and oscillatoxin F (3 ) with Kv1.5 showed oscillatoxin E (2 ) with a strong binding affinity of −37.645 kcal mol −1 and oscillatoxin F (3 ) with a weaker affinity of −32.217 kcal mol −1, further supporting the experimental data.